Beyond Emotions: Unraveling the Role of Emotional and Spiritual Intelligence in Employee Performance - Johari, Bima; Yuniarti, Rina; Ranidiah, Furqonti; Nensi Yuniarti Zs; Astuti, Budi (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study examines the influence of emotional intelligence, spiritual intelligence, and work attitude on employee performance. Understanding these factors is crucial for organizations aiming to enhance productivity. Emotional intelligence relates to self-awareness and emotional regulation, while spiritual intelligence emphasizes purpose and resilience. Work attitude reflects an individual’s perception of their professional responsibilities. A quantitative approach was employed using survey data from employees in a specific organizational setting. Hypothesis testing was conducted through statistical analysis, including t-tests and F-tests, to determine the significance of the relationships among variables. The findings reveal that emotional intelligence does not significantly impact employee performance, indicating that self-awareness alone does not directly enhance productivity. Conversely, spiritual intelligence has a significant positive effect, suggesting that employees with higher spiritual intelligence demonstrate greater resilience, ethical behavior, and motivation. Additionally, work attitude does not significantly influence performance, implying that external factors may have a more substantial role. This study contributes to the literature by emphasizing the importance of spiritual intelligence in improving employee performance. It provides practical insights for organizations to develop programs that foster spiritual intelligence and ethical leadership. Future research should consider additional moderating variables and longitudinal studies to deepen understanding of these relationships.